CSR, SUATU REFLEKSI PERENCANAAN TRANSAKTIF: PERSPEKTIF FILSAFAT ILMU PENGETAHUAN - Muhammad Taufiq; Benedictus Kombaitan; Heru Purboyo Hidayat Putro (TATALOKA, 2018)
This study aims to provide an understanding of why CSR planning does not necessarily bring about community satisfaction even though it has been through participation in its planning, through a philosophical perspective of science. Using evaluative descriptive methods with secondary data sources such as literature and journals (current research), then represented through several focus discussions include: (1) Concept of planning and CSR through the perspective of science philosophy, (2) Ontological, epistemological and axiological aspects of complexity CSR, (3) Theoretical debates, empirical facts and discussions. Conceptual review through this literature review has found the complex connectivity between community and company implicated in understanding that CSR planning is not only participatory planning but also more to transactive planning. In here, CSR understanding tends to transactional, developing value in here is ”who will get something”, not only interpreted as community participation but tended to transactional.